Broadband Microwave Photonic Mixer With High Spurs Suppression and Image Rejection - Gai Shen; Yue Zhou (IEEE Photonics Journal)
A microwave photonic mixer for up- and down-conversion based on dual parallel in-phase and quadrature (I/Q) modulators is proposed. Dual parallel I/Q modulators and 90-degree electrical hybrid couplers are used to obtain carrier-suppressed single-sideband modulation of radio frequency (RF), intermediate frequency (IF), and local oscillator (LO) signals. The optical bandpass filter (OBPF) is employed to select the −1st-order or +1st-order sideband of the LO signal to realize up and down conversion. In the experiments, an IF frequency range of 5–17 GHz can be upconverted to an RF frequency range of 15–37 GHz, and an RF frequency range of 8–40 GHz can be downconverted to an IF frequency range of 2–5 GHz. The spurs suppression ratio exceeds 50 dB for up and down conversion. To the best of our knowledge, this is the highest reported spurs suppression in a broadband microwave photonic mixer. Moreover, the OBPF is also utilized to obtain an image rejection ratio (IRR) of 45.91 dB at an IF frequency of 4 GHz. To obtain a lower frequency of IF signal and a higher IRR, a Brillouin-assisted notch filter is applied to attenuate the image signal. In this way, an IRR of more than 60 dB can be obtained at an IF frequency of 2 GHz.